Volume 6A: Turbomachinery 2013
DOI: 10.1115/gt2013-94311
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Effect of Inflow Distortion on the Performance of a High Aspect Ratio, Low Speed Contra Rotating Fan Stage

Abstract: In this paper, results from an experimental study on the effect of circumferential inflow distorted on the performance and flow behavior of a high aspect ratio, low speed contra rotating fan, are reported. The total pressure at the inlet is artificially distorted by means of 90° mesh sector having porosity of 0.70. The performance of contra rotating fan was studied under variable speed combinations of rotors under clean and distorted inflow conditions. Detailed flow analyses were conducted under design and off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…10,11 To obtain a deeper insight into the flow physics in CRAC, a large amount of work has been carried out on the effects of some major factors such as rotor stagger angle, pitch-chord ratio, inlet distortion, casing treatment, speed ratio of the two rotors, axial spacing between two rotors, etc. [12][13][14][15][16][17][18][19] Results showed that those factors have significant impacts on the performance of CRAC. So as to understand the tip clearance size effect on the overall performance and TLF, Gao et al 20 and Wang et al 21 have conducted steady numerical simulations on several tip clearance sizes for both rotors.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 To obtain a deeper insight into the flow physics in CRAC, a large amount of work has been carried out on the effects of some major factors such as rotor stagger angle, pitch-chord ratio, inlet distortion, casing treatment, speed ratio of the two rotors, axial spacing between two rotors, etc. [12][13][14][15][16][17][18][19] Results showed that those factors have significant impacts on the performance of CRAC. So as to understand the tip clearance size effect on the overall performance and TLF, Gao et al 20 and Wang et al 21 have conducted steady numerical simulations on several tip clearance sizes for both rotors.…”
Section: Introductionmentioning
confidence: 99%
“…Flow field measurements and simulations have shown that distortion leads to a large-scale flow redistribution upstream of a compressor rotor, leading to non-uniform velocity and swirl angles at its leading edge, [20][21][22][23][24]. In many of these studies the rotor is found to operate at high incidence in localised regions of the annulus, with a flow coefficient below the critical clean-flow value, while the machine as a whole remains stable.…”
Section: Introductionmentioning
confidence: 99%
“…Other literature applicable to fan inlet distortion also looked at square waves. Mistry et al [4] carried out experiments on a contra-rotating rotor rig and analysed effects on aerodynamics and performance. Gunn et al [5] conducted experiments on a low speed fan stage and studied the effect on loss mechanisms.…”
Section: Inlet Distortionmentioning
confidence: 99%